Exploring antibiotic resistance load in paddy-upland rotation fields amended with commercial organic and chemical/slow release fertilizer - Han, Bingjun; Shen, Shizhou; Yang, Fengxia; Wang, Xiaolong; Gao, Wenxuan; Zhang, Keqiang (Frontiers in Microbiology, 2023)
Agricultural fertilization caused the dissemination of antibiotic resistance genes (ARGs) in agro-ecological environment, which poses a global threat to crop-food safety and human health. However, few studies are known about the influence of different agricultural fertilization modes on antibiotic resistome in the paddy-upland rotation soils. Therefore, we conducted a field experiment to compare the effect of different fertilization (chemical fertilizer, slow release fertilizer and commercial organic fertilizer replacement at various rates) on soil antibiotic resistome in paddy-upland rotation fields. Results revealed that a total of 100 ARG subtypes and 9 mobile genetic elements (MGEs) occurred in paddy-upland rotation soil, among which MDR-ARGs, MLSB-ARGs and tet-ARGs were the dominant resistance determinants. Long-term agricultural fertilization remarkably facilitated the vertical accumulation of ARGs, in particular that blaampC and tetO in relative abundance showed significant enrichment with increasing depth. It’s worth noting that slow release fertilizer significantly increased soil ARGs, when comparable to manure with 20% replacing amount, but chemical fertilizer had only slight impact on soil ARGs. Fertilization modes affected soil microbial communities, mainly concentrated in the surface layer, while the proportion of Proteobacteria with the highest abundance decreased gradually with increasing depth. Furthermore, microbial community and MGEs were further proved to be essential factors in regulating the variability of ARGs of different fertilization modes by structural equation model, and had strong direct influence (λ = 0.61, P < 0.05; λ = 0. 55, P < 0.01). The results provided scientific guidance for reducing the spreading risk of ARGs and control ARG dissemination in agricultural fertilization.